2021
DOI: 10.1016/j.envres.2021.110999
|View full text |Cite
|
Sign up to set email alerts
|

Geomatics and epidemiology: Associating oxidative stress and greenness in urban areas

Abstract: Green spaces may benefit human health mainly by mitigating noise and air pollution, promoting physical or social activities and improving mental health. Based on the influence that green space exposure seems to exert on Public Health and using a multidisciplinary approach, we investigated, the association between oxidative stress (OS) and green exposure in children. Overall, 207 subjects (10-13 yrs.) living in Torino (NW-Italy) were involved in this study. Each participant provided a urinary sample, used to qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…[48,49] Additionally, the presence of green space promotes physical activity [50,51] and improves cognitive restoration [52] , both associated with functional and epigenetic changes of placental tissue [25,[53][54][55][56] However, the underlying mechanisms of these pathways are still being investigated. A proposed way green space could result in alterations in DNA methylation, might be through their capability to reduce oxidative stress [57][58][59][60] , which is known to impact epigenetic mechanisms. [16,61] Moreover, oxidative stress is hypothesized to be associated with neurodevelopment, supporting the oxidative-stress pathway as a link between green space exposure and methylation changes in neural-related components, such as within the serotonergic pathway.…”
Section: Discussionmentioning
confidence: 99%
“…[48,49] Additionally, the presence of green space promotes physical activity [50,51] and improves cognitive restoration [52] , both associated with functional and epigenetic changes of placental tissue [25,[53][54][55][56] However, the underlying mechanisms of these pathways are still being investigated. A proposed way green space could result in alterations in DNA methylation, might be through their capability to reduce oxidative stress [57][58][59][60] , which is known to impact epigenetic mechanisms. [16,61] Moreover, oxidative stress is hypothesized to be associated with neurodevelopment, supporting the oxidative-stress pathway as a link between green space exposure and methylation changes in neural-related components, such as within the serotonergic pathway.…”
Section: Discussionmentioning
confidence: 99%
“…From an ecosystem service perspective, vegetation may provide shade, reduce heat, and contribute to an inviting setting for physical activity and social interaction. As such urban green space could have long-term human health benefits (Salmond et al 2016;Aerts et al 2018;Bratman et al 2019;Engeman et al 2019;Zhang et al 2021), including lower probabilities for mood disorders (Barwise and Kumar 2020;De Petris et al 2021) and lower counts of mood disorder treatments (Nutsford et al 2013). For instance, Taylor et al (2015) found an inverse association between street tree density and prescriptions for antidepressants in London.…”
Section: Introductionmentioning
confidence: 99%
“…Signaling in the central nervous system (CNS) is terminated by the clearance of neurotransmitters from the synapse via high-affinity transporter molecules in the presynaptic membrane [ 73 ]. Accumulated evidence has shown that exposure to greenness has a positive effect on health by reducing oxidative stress [ 74 , 75 , 76 , 77 ]. Additionally, oxidative-stress-induced damage to the brain is likely to negatively affect normal CNS functions [ 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, oxidative stress is widely related to brain development. Recently, greenness exposure was significantly associated with reduced oxidative stress in Italian children [ 75 ]. We suggested that exposure to greenness, which was a pathway to reducing oxidative stress, may be involved in neurodevelopment.…”
Section: Discussionmentioning
confidence: 99%